The Declaration of the Establishment of the State of Israel: Reflections on its Sixtieth Anniversary - Cohen, Raymond; Weissman, Deborah; Bernauer, SJ, James; Korn, Eugene; Lautt, OP, Ruth; Greenspoon, Leonard; Rudnick, Ursula; Hale, Dennis; Pettit, Peter; Weiman, Racelle (Studies in Christian-Jewish Relations, 2011)
No abstract is available.